Isolasi dan karakterisasi bakteri berpotensi probiotik pada ikan kembung (Rastrelliger sp.) - Yuni Dewi Safrida; Cut Yulvizar; Cut Nanda Devira (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2012)
Abstract. Probiotics bacteria are beneficial microbes to improve microbial balance in the digestive tract. The objective of the research was to isolate and characterize of potential probiotic bacteria in mackerel fish (Rastrelliger sp.). The research was done from April to August 2012 at Laboratory of Microbiology Syiah Kuala University, Banda Aceh. Isolation and characterization used dilution and scratches quadrant methods. The result showed that there were five potential isolates of probiotic bacteria varied morphological colony and cell. The isolate have circular form (100%), entire margin (80%), flat (60%), cream color (40%), gram positive bacteria (80%), coccus shape (100%) and non motile (60%).Keywords: Probiotics, Rastrelliger sp., isolation, digestive and characterization